The Influence of Country of Origin and Brand Image on Vivo Smartphone Purchase Decisions with Word of Mouth as a Moderation Variable: A Study on Vivo Smartphone Users in Sampit City - Seanewati Oetama; Hari Susanto; Yolan Della Tasya (Lembaga Publikasi Ilmiah Nusantara, 2026)
This study was conducted in Sampit City to examine the influence of Country of Origin and Brand Image on Vivo smartphone purchase decisions, with Word of Mouth (WOM) as a mediating variable. The research involved 65 Vivo smartphone users selected through accidental sampling. Data were collected using questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with WarpPLS 4.0. The analysis included validity and reliability testing, evaluation of the outer and inner models, and hypothesis testing. The results showed that the R² value for WOM was 0.415, indicating that Country of Origin and Brand Image explained 41.5% of the variation in WOM. The R² value for Purchase Decision was 0.430, indicating that the model explained 43.0% of the variance in purchase decisions. Country of Origin had no significant direct effect on Purchase Decision (t = 1.209; p = 0.227), whereas Brand Image and WOM did. WOM significantly mediated the relationship between Country of Origin and Purchase Decision (t = 2.367; p = 0.018), but did not mediate the relationship between Brand Image and Purchase Decision. The novelty of this study lies in integrating Country of Origin, Brand Image, and WOM within a single model to explain smartphone consumer behavior in a regional market context. The findings demonstrate that WOM strengthens the influence of product-origin perceptions on purchase decisions, while Brand Image remains a key determinant of consumer purchasing behavior.